2019
DOI: 10.1016/j.joto.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dilation of Eustachian tube combined with tympanostomy tube insertion and middle ear pressure equalization therapy for recurrent secretory otitis media

Abstract: Objective to report outcomes of balloon dilation Eustachian tuboplasty combined with tympanostomy tube insertion and middle ear pressure equalization therapy in treatment of recurrent secretory otitis media. Methods Fifty one patients with recurrent secretory otitis media (62 ears) underwent balloon dilation of Eustachian tube and tympanic tube insertion under general anesthesia, followed by long term middle ear pressure equalization therapies. The Eustachian tube score (ETS) and Eustachian tube function quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In our study, patients treated with BET and grommet insertion had a satisfying outcome in terms of their subjective symptoms and objective evaluations, and also achieved good results in eustachian tube function and structure, which is consistent with the findings of Yin et al (22). The quantitative examination peak pressure deviation of eustachian tube function significantly increased postoperatively (P<0.05), as did the ETS.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, patients treated with BET and grommet insertion had a satisfying outcome in terms of their subjective symptoms and objective evaluations, and also achieved good results in eustachian tube function and structure, which is consistent with the findings of Yin et al (22). The quantitative examination peak pressure deviation of eustachian tube function significantly increased postoperatively (P<0.05), as did the ETS.…”
Section: Discussionsupporting
confidence: 90%
“…Understanding ETDQ‐7 scores and tympanometry for a large cohort of individual patients presenting to an otolaryngology clinic would allow for a more robust assessment of the predictive power of ETDQ‐7. However, based upon the currently available evidence, it is unlikely that future studies would support the use of EDTQ‐7 scores as a substitute for tympanometry or other objective measures in diagnosing ETD 43‐47 …”
Section: Discussionmentioning
confidence: 99%
“…However, based upon the currently available evidence, it is unlikely that future studies would support the use of EDTQ‐7 scores as a substitute for tympanometry or other objective measures in diagnosing ETD. 43 , 44 , 45 , 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Selection bias may have influenced this difference as patients with more severe pathology were directed toward the OR. In addition, when FESS with ethmoidectomy or tympanic membrane repair were performed, patients were asked to refrain from Valsalva or nose-blowing for 2 weeks, which might affect the early aeration of the ET 20. Prior studies have reported limitations in performing BDET due to pain.…”
mentioning
confidence: 99%